1997
DOI: 10.1046/j.1365-2133.1997.19552041.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma, malignant melanoma and malignant fibrous histiocytoma arising in burn scars

Abstract: The most common cancer arising from an old burn scar is squamous cell carcinoma, while malignant melanoma is rare. There are only four reports in the literature on the combination of the more common tumour with a malignant melanoma and only two cases of malignant fibrous histiocytoma alone. This paper reports the first occurrence of the combination of all three types of cancer in burn scars of the same patient. The factors that promote malignant transformation, such as immunological factors and karyotype, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…As with burn scar cancers, tumours often start at an ulcer margin and only one portion of the ulcer may undergo malignant change, whilst the rest remains a non-healing inflamed area. [18][19][20] Therefore, it is often essential to perform multiple biopsies to avoid missing occult malignancy. In addition, regional lymph node examination is important because if lymphadenopathy is detected it may warrant a fine needle aspiration or lymph node biopsy.…”
Section: Do Eb Patients Have An Increased Risk Of Extracutaneous Malimentioning
confidence: 99%
“…As with burn scar cancers, tumours often start at an ulcer margin and only one portion of the ulcer may undergo malignant change, whilst the rest remains a non-healing inflamed area. [18][19][20] Therefore, it is often essential to perform multiple biopsies to avoid missing occult malignancy. In addition, regional lymph node examination is important because if lymphadenopathy is detected it may warrant a fine needle aspiration or lymph node biopsy.…”
Section: Do Eb Patients Have An Increased Risk Of Extracutaneous Malimentioning
confidence: 99%
“…By reviewing the 18 previously documented cases (Table I), we identified that the patient age range was 32–94 years and only 6 cases occurred in individuals aged ≤55 years (2,7,8,12). No predominant gender predilection has been noted for SMT variants.…”
Section: Discussionmentioning
confidence: 99%
“…Double tumors comprising SCC and BCC (2%) and SCC with melanoma[2] (1%) have also been reported. A rare report of three malignancies developing in the same patient[3] has been described. Literature reports only two cases of epithelioid sarcoma in a burn scar[4] and the present case is the first case report of epithelioid sarcoma along with SCC in a burn scar.…”
Section: Discussionmentioning
confidence: 99%